The Value of Simulation in Interventional Radiology - Barnett, Christopher J.; Pua, Bradley B. (Digestive Disease Interventions, 2020)
Medicine has increasingly incorporated simulation training amidst improving simulation technologies and evolving educational perspectives. This article examines the broad concept of simulation in medicine to focus, in particular, on its multifaceted value for providers and patients within the field of interventional radiology. Simulation technology ranges in degrees of fidelity, with new advancements notably in high-fidelity endovascular simulation, as well as in augmented and virtual reality. Current evidence on the validity of simulation within interventional radiology is promising, spanning training, credentialing, preprocedural planning, and team-building applications.
Keywords: simulation training; medical education; interventional radiology